The Impact of the Syrian Refugee Crisis on the Civil Society Sector in Lebanon - El Chmali, Laura (Border Crossing, 2017)
This article is driven by an interest to explore the role of local Civil Society Organizations (CSOs) and community-based organizations (CBOs) that deal with Syrian refugees in Lebanon seeing the void left by the Lebanese weak state to cope with this situation. How the Syrian conflict has affected the civil society landscape in Lebanon and how the inflow of international aid has affected the work of this local CSOs, as well as, their relationship with Lebanese state authorities on the national and local levels are examined. To this extent, the ways in which the management of Syrian refugees by local CSOs and CBOs has been affected by external factors, including the Lebanese government policies and the role of international organizations (EU, UN) in managing the crisis in Lebanon are examined. Since the beginning of the Syrian conflict and the influx of millions of refugees into Lebanon, the civil society sector in Lebanon has undergone significant transformations. To cope with the overwhelming number of Syrians living in Lebanon, Lebanese civil society has expanded with the creation of new CSOs as well as the introduction of additional programs and projects in existing CSOs to assist refugees. These civil society organizations fill a void created by the Lebanese government in its unwillingness or inability to assist with the refugee response in the areas of healthcare, education and vocational training.